The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2478/s11756-009-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Floristic composition and conservation value of the stubble-field weed community, dominated by Stachys annua in western Hungary

Abstract: Abstract:The stubble-field weed community, dominated by Stachys annua, was generally distributed in Hungary until the 1950s on mid-heavy and heavy, base-rich soils. Stachys annua is an excellent nectar-producer, and from the nectar collected in its habitats popular stubble-honey was produced. This vegetation type has suffered significant decline, mainly due to the early ploughing of stubbles associated with the intensification of agriculture. In the present study, the floristic composition of this community is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
1
14
1
3
Order By: Relevance
“…). Weeds in unploughed stubble can have special conservation value as food sources for insects and birds, and the early stubble ploughing that accompanies arable intensification typically prevents completion of their life cycle (Pinke & Pál ). A study of summer annual weed vegetation (including stubble) also found decreasing effects of intensive crop management towards the field periphery (Pinke et al.…”
Section: Introductionmentioning
confidence: 99%
“…). Weeds in unploughed stubble can have special conservation value as food sources for insects and birds, and the early stubble ploughing that accompanies arable intensification typically prevents completion of their life cycle (Pinke & Pál ). A study of summer annual weed vegetation (including stubble) also found decreasing effects of intensive crop management towards the field periphery (Pinke et al.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive agricultural management, mainly with the use of chemicals and early ploughing of stubbles, has largely impoverished the weed diversity of cereal ecosystems. Low-input systems however can possess great conservational values and it is within these habitats that the relationship between weed vegetation and environmental factors can still be studied [1,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Holub and Procházka, 2000;Pyšek, 2001;Ruprecht, 2005), and inappropriateness of habitats for natural enemies, birds and mammals (Seifert et al, 2015). These communities are drastically influenced by new intensive agronomical systems (Kropáč, 2006) and Pinke and Pál (2009) consider the increasing of ragweed spread either as one of the reasons.…”
Section: Resultsmentioning
confidence: 99%
“…In general many segetal plants in Central Europe are threatened by extinction (Kropáč, 2006) and increasing spread of common ragweed pose the threat e.g. to stubble-field weed community (Pinke and Pál, 2009). …”
Section: Abstraktmentioning
confidence: 99%